Growth, fat metabolism and hepatic health in largemouth bass fed varying fat-level diets - Digen Qin; Jiale Chen; Junxiong Li; Zhiyou Liu; Weibin Huang; Yuanzhi Yang; Jing Zhang; Beiping Tan; Xiaohui Dong (Aquaculture Reports)
This 60-day experiment investigated the influences of growth, fat metabolism and hepatic health of largemouth bass (Micropterus salmoides) fed varying fat diets. 225 fish (34 ± 0.04 g) were divided into three groups and fed diets with fat levels of 10 % (Low-fat diet, LFD), 14 % (Medium-fat diet, MFD) and 18 % (High-fat diet, HFD), respectively. The results revealed that fish fed HFD exhibited significantly better protein efficiency ratio (PER) and lower feed conversion ratio (FCR) than LFD group (P<0.05), but survival rate (SR) and weight gain rate (WGR) were unaffected (P>0.05). Dietary fat levels significantly decreased hepatosomatic index (HSI) of fish (P<0.05), but visceral somatic index (VSI) and condition factor (CF) were unaffected (P>0.05). The contents of fat and ash in whole-body, and hepatic fat contents were increased with dietary fat levels (P<0.05), the contents of moisture and crude protein in whole-body and liver exhibited no substantial variations (P>0.05). Serum biochemical indexes and serum alanine aminotransferase (ALT) activity, liver glutathione peroxidase (GSH-Px) and catalase (CAT) activities were increased significantly with rising dietary fat levels (P<0.05), serum aspartate transaminase (AST) and liver superoxide dismutase (SOD) activities had no statistical differences (P>0.05). The expression of srebp-1 and acc in liver were down-regulated, but atgl, aco and bax were up-regulated with rising dietary fat contents (P<0.05). Caspase-3 exhibited a remarkable tendency of initially rising and then declining (P<0.05), the expression of fas, cpt-I, bcl-2 and the ratio of bcl-2/bax were unaffected (P>0.05). The histology of liver indicated the size and quantity of fat droplets increased with increment of dietary fat intake. Conclusion: the dietary fat levels of 14 %-18 % could be conducive to better growth of largemouth bass in this study.